Influence Of Marketing Strategy And Service Quality On Purchase Decisions Through Consumer Satisfaction As Intervening Variables In Hotel Permata Land Rantau Prapat - Dame Masterina, Olivia; Pakpahan, Efendy; Ariesa, Yeni; Syaifuddin, Syaifuddin (International Journal of Science, Technology & Management, 2022)
The purpose of this study was to determine the effect of service quality on purchasing decisions through customer satisfaction at Hotel Permata Land Rantau Prapat. The number of samples taken in this study using the Lemeshow formula, namely 96 people. Determination of the sample in this study was carried out by non-probability sampling. The method used is path analysis. Based on the results of the study, it was found that the marketing strategy had a significant positive effect on the purchasing decision of Permata Land Hotel. Service quality has a significant positive effect on purchasing decisions, marketing strategy has a significant positive effect on consumer satisfaction, then service quality has a significant positive effect on consumer satisfaction, consumer satisfaction has a significant positive effect on purchasing decisions, marketing strategy has a significant positive effect on consumer satisfaction at Permata Land Hotel. The results of this study indicate that the better the marketing strategy carried out by the company affects purchasing decisions so that the level of consumer satisfaction will be high, it can be seen from the value of the significant results of marketing strategies that affect purchasing decisions through customer satisfaction obtained. Service quality has a significant positive effect on purchasing decisions through customer satisfaction.